Pengaruh Pandangan Hidup Islam terhadap Kepemimpinan Etis dalam Konteks Manajerial - Armelia, Syifa; Sintia, Nesa (AGUSPATI RESEARCH INSTITUTA, 2024)
The worldview serves as a foundation in character building and decision-making, including in leadership. The research method used is descriptive qualitative, by collecting data from related sources, including analysis from Prof. Dr. Hamid Fahmy Zarkasy. The results show that the Islamic worldview, which includes three pillars: Islam, Iman, and Ihsan, has a significant influence on leaders' behavior and decisions. The values of honesty, justice, and compassion in Islam shape a positive and ethical work culture, so that leaders can create an environment that supports high performance. The outcome of this study is that leaders who internalize Islamic values can improve employee well-being and strengthen team commitment, ultimately contributing to better and sustainable organizational performance. The purpose of this article is to explore how an Islamic worldview can influence ethical leadership in a managerial context, as well as to demonstrate the importance of Islamic values in shaping ethical leader behavior and organizational culture.